International consensus definition of DNA methylation subgroups in juvenile myelomonocytic leukemia - Schönung, Maximilian; Meyer, Julia; Nöllke, Peter; Olshen, Adam B.; Hartmann, Mark; Murakami, Norihiro; Wakamatsu, Manabu; Okuno, Yusuke; Plass, Christoph; Loh, Mignon L.; Niemeyer, Charlotte; Muramatsu, Hideki; et al. (Clinical cancer research, 2021)
Known clinical and genetic markers have limitations in predicting disease course and outcome in juvenile myelomonocytic leukemia (JMML). DNA methylation (DNAme) patterns in JMML have correlated with outcome across multiple studies, suggesting it as a biomarker to improve patient stratification. However, standardized approaches to classify JMML based on DNAme patterns are lacking. We therefore sought to define an international consensus for DNAme subgroups in JMML and develop classification methods for clinical implementation.
Published online first on November 2, 2020
Gesehen am 08.01.2021